There Is No Crime for Those Who Have Christ: Religious Violence in the Christian Roman Empire - Gaddis, Michael (The transformation of the classical heritage, 2005)
Preface and Acknowledgments; List of Abbreviations; Introduction; 1. "What has the emperor to do with the church?" Persecution and Martyrdom from Diocletian to Constantine; 2. "The god of the martyrs refuses you": Religious Violence, Political Discourse, and Christian Identity in the Century after Constantine; 3. An Eye For An Eye: Religious Violence in Donatist Africa; 4. Temperata Severitas: Augustine, the State, and Disciplinary Violence; 5. "There is no crime for those who have Christ": Holy Men and Holy Violence in the Late Fourth and Early Fifth Centuries